Sejarah Perkembangan Institusi Pendidikan Islam di Aceh Dari Abad Ke-16 Sehingga Abad Ke-19: History of the Development of Islamic Educational Institutions In Aceh From 16th Century to the 19th Century - Mohd Bakri, Mohamad Fikri; Ishak, Muhammad Farhan; Baharom, Adlin Shaimi (Journal Al-Muqaddimah, 2024)
The 16th century was the golden age of the Sultanate of Aceh Darussalam after the fall of the Malacca Malay Kingdom. The arrival of Islam to Aceh has been welcomed by the local population. Therefore, along with the passage of time, Aceh has reached its glory phase under the rule of Sultan Iskandar Muda. During his reign, various Islamic educational institutions have appeared such as the Balai Setia Ulama, Balai Setia Hukama, Jamaah Himpunan Ulama, meunasah and mosques. With the establishment of this Islamic institution, various Islamic scholars were successfully born such as Hamzah Fansuri and Syamsuddin al-Sumaterani. The development of Islamic educational institutions in Aceh clearly shows the efforts made by Sultan Iskandar Muda to make Islam a way of life in Acehnese society. This study discusses the development of Islamic educational institutions in Aceh from the 16th century to the 19th century and also its contribution to the Islamic world. This study is a qualitative study that uses a library research approach. From the aspect of data collection, it uses documentation methods and data analysis using text and content analysis methods.